KINERJA KEUANGAN PT MAHIR JAYA MAHAKAM DI SAMARINDA - Ekawati, Diah (EKONOMIA, 2013)
Generally every company using ratio analysis to measure the performance of the company. Analysis of this ratio is the most important in measuring the development of a business and to compare a business with competitors and express meaningful relationships among the components of the financial statements, the purpose of this study Knowing the financial performance. of PT Mahir Jaya Mahakam Raya Samarinda in 2009, 2010 and 2011 when measured by the ratio of liquidity, solvency and profitability. Basic theory used by the Financial Accounting using the financial ratio analysis tool.Based on the analysis and discussion of the conclusions of this study as follows: Judging from the company's liquidity, then of PT Mahir Jaya Mahakam RayaÂ has to be said as well Cas liquid ratio, current ratio, Quick Test Ratio from 2009 to 2010 and to 2011 increased so the hypothesis is rejected.Judging from the solvency of the company, of PT Mahir Jaya Mahakam Raya Samarinda can be said as well insolvabel Total Debt to Total Assets Ratio and Total Debt to Total from 2009 to the year 2010 to 2011 saw strong improvement and decline, which means unstable, so the hypothesis is accepted.Views of profitability, of PT Mahir Jaya Mahakam Raya shows instability seen as Net Profit Margin, Return on Investment and Return on Equity in 2011 has decreased, so the hypothesis is accepted.